Amorphous MoO3−x nanosheets prepared by the reduction of crystalline MoO3 by Mo metal for LSPR and photothermal conversion. Issue 83 (2nd October 2019) - Guo, Cang; Yan, Pengfei; Zhu, Chuanhui; Wei, Cong; Liu, Wei; Wu, Wenzhuo; Wang, Xuzhe; Zheng, Lirong; Wang, Jiaou; Du, Yi; Chen, Jun; Xu, Qun
Abstract : Amorphous MoO3− x nanosheets with enhanced LSPR are fabricated by introducing Mo atoms into the interlayers of MoO3 via a hydrothermal and post-irradiation method, which is beneficial for photo-to-heat conversion. Abstract : Amorphous MoO3− x with enhanced LSPR has been fabricated successfully by introducing Mo atoms into the interlayers of MoO3 nanosheets via a hydrothermal method. The inserted Mo atom could bond with inherent Mo atoms and further form a distorted atomic configuration structure. Thus, the amorphous MoO3− x possesses a relatively excellent photothermal conversion efficiency of 61.79%.